Crowdfunding no Brasil : um estudo sobre a plataforma Catarse - Aguiar, Carlos Eduardo Magalhães Vieira de (Universidade Federal de São Carlos, 2016)
At the end of the twentieth century and early twenty-first century, with the advent of digital technologies, the proliferation of the Internet and the cheapening of audiovisual equipment, new options have emerged to produce, distribute and show films. Among these options, highlight the practice of crowdfunding, one of crowdsourcing models, as an alternative possibility of national film funding. Nevertheless crowdfunding still a recent practice and little known in the country, with many platforms being launched and also closed, and the vast majority of funded projects are especially concentrated in the southeast region. This thesis sought to discuss this scenario, taking as its starting point the authors Jeff Howe and Henry Jenkins, and also Brazilian academic research on crowdfunding published until August 2015. The study subjects were the online community Crowdfunding BR and Brazilian platform of crowdfunding Catarse, focusing on projects of this platform in the category named Film and Video. The result indicates datas able to expand the reader's understanding and stimulate critical view of this practice, based on the presentation of its origins, organization mode, propagation around the world and it insertion in Brazil, making possible the understanding of the current context and the potential not yet explored of crowdfunding in the country.
Keywords: Crowdfunding; Crowdsourcing; Financiamento coletivo; Financiamento colaborativo; Financiamento da multidão; Collective financing; Collaborative funding; Film and Video; Movies; Brazilian cinema; Catarse; Crowdfunding BR; LINGUISTICA, LETRAS E ARTES